Rings of functions on non-abelian groups - Maxson, C.J. (Algebra and Discrete Mathematics, 2009)
For several classes of finite nonabelian groups we investigate the structure of the ring of functions, R(C), determined by the cover C of maximal abelian subgroups. We determine the Jacobson radical J(R(C)) and the semisimple quotient ring R(C)/J(R(C)).